IDENTIFY OPPORTUNITIES FOR RETAIL'S VIEW ONLINE AND BUY OFFLINE (ROPO) MODEL (Marketing Journal, 2025)
The article examines the impact of digital technologies on retail trade and the significance of the ROPO model (Research Online, Purchase Offline). A comparative analysis of international practices (Germany, the UK, Poland, etc.) has been conducted, alongs ide an assessment of the potential for implementing the ROPO model in the context of Uzbekistanʼs retail market. A SWOT analysis was applied to identify the strengths, weaknesses, opportunities, and threats of the model.
Keywords: retail trade; digital technologies; ROPO model; e -commerce; omnichannel strategy; SWOT analysis